2019
DOI: 10.15802/stp2019/165160
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dynamic Indicators of Flat Wagon With Load Centre Shift

Abstract: Purpose. The article deals with the determining the influence of the longitudinal and lateral shift of gravity centre of the heavy load on the flat wagons, taking into account the travel speed based on the main dynamic indicatorsthe maximum coefficients of the dynamic supplement of spring-suspended and unsprung parts, the maximum ratio of frame force to static axle load, the wheel derailment safety factor. Methodology. The study was carried out using the method of mathematical and computer simulation of the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In our research we studied the effect of the load mass center shift on the flat car frame in the longitudinal х А and transverse directions х А , as well as in both directions simultaneously. Preliminary theoretical studies have shown that in the presence of a transverse or simultaneous transverse and longitudinal displacement of the load mass center over 0.15 у А  m there is a sharp decrease in the derailment coefficient and a high probability of rolling stock derailment [21]. In order to determine the effect of only the load mass centre displacement on the factor of wheel and rail wear, the displacement in the transverse and simultaneous transverse and longitudinal directions is considered within the limits .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research we studied the effect of the load mass center shift on the flat car frame in the longitudinal х А and transverse directions х А , as well as in both directions simultaneously. Preliminary theoretical studies have shown that in the presence of a transverse or simultaneous transverse and longitudinal displacement of the load mass center over 0.15 у А  m there is a sharp decrease in the derailment coefficient and a high probability of rolling stock derailment [21]. In order to determine the effect of only the load mass centre displacement on the factor of wheel and rail wear, the displacement in the transverse and simultaneous transverse and longitudinal directions is considered within the limits .…”
Section: Methodsmentioning
confidence: 99%
“…With these models, it is possible to obtain solutions for various types of wheel-rail contact, to take into account the rigidity of the structural elements and the various deviations from the initial configuration of the system, such as the misalignment of the wheel set axles in the bogie, the difference in the wheel radii of one wheel set, of different wheel sets in a bogie and different bogies, rail gradient and wheel profile of various types, change in the cross gap of the wheel set and rail track, the change of longitudinal and cross clearance between the axle-boxes and side frames, the displacement of the body mass center relative to the car symmetry, etc. [5,13,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the forces transmitted to the wagon parts when moving along the curve, and the forces caused by changes in speed and body oscillations, it is necessary to reduce the center of mass of the wagon and reduce its displacement from the vertical symmetry axis. A decrease in the center of mass is also advisable for freight wagons with a relatively short bogie center distance [11][12][13][14]. In trains the longitudinal forces sometimes reach a value exceeding the strength of the frame of some wagon designs.…”
Section: Strength Of Rolling Stock Elementsmentioning
confidence: 99%
“…For a further supplement to loading guidelines, the method of dynamics simulation has been used to search for the safe range of wagon's gravity center. Shatunov and Shvets [15] proposed that, as for a kind of 4-axle flat wagon, the maximum lateral offset could reach 150 mm and longitudinal offset could be expanded too. Bao et al [16] focused on a common open-top wagon in China and demonstrated that CR criteria were conservative.…”
Section: Introductionmentioning
confidence: 99%